Validity of BI-RADS System Mammography to detect breast cancer at Dr Sardjito Hospital Yogyakarta - Teguh Aryandono, Indrasto Histopaedianto Lina Choridah (Universitas Gadjah Mada, 2008)
Background: Breast cancer is the second most common cancer among women worldwide and the sixth common cause of mortality in Indonesia. The diagnosis of breast cancer may be established by physical and imaging examinations, but definitive diagnosis should be verified by histopathologic examination. Mammography is an easy non-invasive imaging method to detect breast cancer with good accuracy. The lack of uniformity in mammography reporting has led to confusion as to the interpretation and management recommendation. The American College of Radiology Breast Imaging Reporting and Data System (BIRADS) has provided a standardized reporting system for mammography. The validity of this system at Dr Sardjito Hospital Yogyakarta has not been evaluated.Objective: To know the sensitivity, specificity, positive and negative predictive values, and accuracy of the BI-RADS System Mammography in diagnosing breast cancer.Methods: This study was a diagnostic test with cross sectional design on breast cancer diagnosis based on BI-RADS system mammography. All medical record files of patients with breast lump who underwent mammography and histopatologic examination, at Dr Sardjito Hospital Yogyakarta between December 2003-March 2008, were included in the analysis.Results: BI-RADS System Mammography at Dr Sardjito Hospital Yogyakarta had sensitivity of 87.5%, specificity of 93.7%, positive predictive value of 96.5%, negative predictive value 78.95%, positive likelihood ratio 14, negative likelihood ratio 0.13, prevalence 66.6%, and accuracy 89.6%.Conclusion: Mammography examination using BI-RADS System in Sardjito Hospital Yogyakarta was favourable in detecting breastcancer.Key words: breast cancer - BI-RADS mammography - histopathology - diagnostic value